A Survey of Macrozoobenthos Assemblages in a Tropical Mangrove Estuary in Brebes, Java Island - Sheila Zallesa; Indah Riyantini; Sri Astuty; Yusuf Arief Nurrahman; Ibnu Faizal; Sulastri Arsad; Marine K Martasuganda; Fiddy Semba Prasetiya (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
The mangrove forest in Brebes is one of the mangrove areas that were degraded due to abrasion and excessive logging in the North Coast of Java Island, Indonesia. This research aimed to analyze macrozoobenthos community structure in the mangrove forest that has not been documented. Surveys were carried out in the rainy season. In this study, a total of 10 sampling locations were divided into two different groups that represent “control” (station) and “disturbed” sites. The main structural parameters of the macrozoobenthos identified at each station were specific richness S (number of species), abundance N (number of individuals.m-2), the Shannon-Wiener index N1. A total of 346 specimens were counted from the two different stations (“control” and “disturbed”). These specimens were belonged to five animal classes, namely, Bivalvia, Gastropod, Malacostraca, Polychaeta, Cephalopoda. Pairwise comparison of the site groups with one-way analysis of similarity (ANOSIM) was not significant for between “control” and “disturbed” groups (p=0.062), where the average dissimilarity between the two stations was 88.42%. This result provides macrozoobenthos diversity and ecological information that may contribute to further conservation management in the mangrove forest in Brebes, Indonesia.